Single Administration of a Biodegradable, Separable Microneedle Can Substitute for Repeated Application of Eyedrops in the Treatment of Infectious Keratitis. Issue 11 (30th April 2021) - Park, SeungHyun; Lee, KangJu; Kang, Heekyoung; Lee, YeJin; Lee, JiYong; Kim, Jeong Hun; Song, Hyun Beom; Ryu, WonHyoung
Abstract: Infectious keratitis is mainly treated with topical antibiotics. To achieve and maintain the required therapeutic concentration in the cornea where the tear fluid continuously rinses the surface, the antibiotics must be frequently applied, even while the patient is sleeping, and oral medication is sometimes required. However, the inevitably poor compliance and avascular nature of the cornea decrease drug bioavailability. In this study, a single microneedle (MN) is injected into the cornea to substitute for the repeated application of eyedrops in the treatment of infectious keratitis. After comparing the mechanical integrity and drug release profiles of three different drug‐tips, the drug‐tip with the "high" drug concentration that releases 12.5 ng drug within 3 days is applied to a cornea to evaluate the transferability and in vivo drug release. In the treatment of infectious keratitis with repeated application of eyedrops for six consecutive days, a single MN injection is substituted for the initial 3 days of eyedrop applications. The progression remains similarly attenuated after 3 days without eyedrops, and comparable efficacy is achieved on day 6 when combined with delayed eyedrop treatment from day 3. Thus, the single administration of a biodegradable MN can substitute for the repeated application of eyedrops in the treatment of infectious keratitis. Abstract : Biodegradable and separable microneedle into the cornea is studied for a substitute for multiple eyedrops in the treatment of infectious keratitis. This study introduces the mechanical integrity and release optimization with three different formulations of drug‐tip, and demonstrates that a single microneedle injection can substitute for initial 3 days of multiple eyedrops by efficacy comparison in vivo.